PENGARUH CAPACITY BUILDING GAMES TERHADAP PENGETAHUAN DAN SIKAP ANAK PANTI ASUHAN TENTANG KESEHATAN REPRODUKSI - Niken Agus Tianingrum; Lia Kurniasari; Nida Amalia (Dian Nuswantoro Semarang, 2020)
Health reproductive become an attractive issue among adolescent, but not all of them have the right access of information because of different condition, such as an orphans, who live under foster parents and have limited access on health information. It needs an activity that can increase their capacity to overcome the fluctuation of adolescent world, especially to take control over their reproductive health. This research is a pre experimental with 40 participants of adolescent aged 12-18 years old, conducted in orphanage in Samarinda City. The interventions include play snake and ladder, flash card and role play. Data were collected by validated questionnaire to measure knowledge and attitude, then analyzed by paired t test. Results show that there is significant influence of snake and ladder and flash card toward knowledge (p=0.017; r = 0,724; CI 95% = 0,115-1,084; SD = 1,515) and also significant influence of role play toward (p =0,049; r = 0,604; CI 95% = 0,003-1,097; SD = 1,709). It is hoped that orphanage can facilitate their foster child with interactive media to increase their capacity of life, especially reproductive health.Keywords: Snake and ladder, Flash Card, Role Play, knowledge, attitude